Sommersby - Amiel, Jon (Philippines : Warner Home Video, 1993)
The moment Jack Sommersby (Richard Gere) emerges from the wilderness to reclaim his life after a seven-year absence, he brings dramatic change to his home town and everyone in it. When the young plantation owner, departed Vine Hill, Tennesse to fight in the Civil War, he left behind a wife and infant son, and friends and acquaintances who saw him leave with mixed emotions. Sommersby has been a difficult man, often crude, violent and ineffectual in overseeing his lands. HIs wife, Laurel (Jodie Faoster) felt the strain of running plantation on her own, raising a child and surviving a devastating war, but she also felt the relief of freedom from Sommersby's coldness and occasional brutality. A family friend, Orin Meecham (Bill Pullman), saw the opportunity to court Laeurel when Sommersby did not principled Laurel would consider her husband officially dead and would marry Orin. But when Jack Sommersby returns, more two years after the end of the war, he is a different man. And no one can envision the great joy and profound sadness the lie ahead. Sommersby rekindles the love that once drew Laurel to him, showing himself to be at once gentler and more passionate than she ever remembered. He turns the tide of poverty in Vine Hill, bringing the entire town back to prosperity by pioneering the cultivation of tobacco. His transformation, in fact, is so complete that people begin to wonder if Jack Sommersby could possibly be the same man who left town seven years ago. And only his adoring wife, Laurel, knows the secrets that Sommersby carries within him.